Study on the floral scent components of Lilium amoenum with rose fragrance and Lilium bakerianum var. rubrum with orange fragrance - ZHENG Ranran; WU Jingzhi; GU Zhijia; YUAN Wenbin; WU Hongzhi (浙江大学学报. 农业与生命科学版)
Headspace-solid-phase microextraction (HS-SPME) and gas chromatography-mass spectrometry (GC-MS) combined techniques were used to analyse qualitatively and quantitatively the volatile substances of five different types of lilies. The results showed as follows: 33 and 26 kinds of floral scent components were identified from two light sweet fragrance wild lilies of Liliumamoenum with rose fragrance and L. bakerianum var. rubrum with orange fragrance, respectively; 30 kinds of floral scent components were identified from wild L. souliei with strong smell; 27 and 34 kinds of floral scent components were identified from the cultivars of ‘Siberia’ (O) and ‘Robina’ (OT) with strong smell, respectively. Among the lilies with light sweet fragrance, the main floral components of L. amoenum were linalool (15.42%), (Z )-3-hexen-1-ol, acetate (9.93%), eucalyptol (7.54%), α-farnesene (7.05%), etc; the main floral scent components of L. bakerianum var. rubrum were linalool (46.38%), Cis-β-ocimene (33.08%), β-myrcene (4.75%), etc. Among the lilies with strong smell, the main floral scent components of L. souliei were dl-limonene (45.31%), linalool (13.57%), benzeneacetaldehyde (4.01%), etc; the main floral scent components of ‘Siberia’ were linalool (48.53%), methyl benzoate (23.24%), Cis-β-ocimene (13.99%), isoeugenol (6.12%), etc; the main floral scent components of ‘Robina’ were Cis-β-ocimene (33.43%), eucalyptol (11.93%), methyl benzoate (10.27%), methyl salicylate (8.21%), isoeugenol (7.67%), linalool (6.92%), etc. Terpenes were the main type of floral scent components in the five lilies, and linalool was the main floral scent component in the five lilies. Methyl benzoate, methyl salicylate and other esters had relatively high contents in the ‘Siberia’ and ‘Robina’. In conclusion, rose fragrance in L. amoenum may come from α-farnesene, and orange fragrance in L. bakerianum var. rubrum may come from β-myrcene.